“BACTERIOPHAGE THERAPY” AN EMERGING CURE FOR BACTERIAL DISEASE - GUPTA, TEJASV; KANCHAN; BHAGYAWANT, SAMEER S. (International Journal of Current Pharmaceutical Research, 2023)
Bacteriophages are viruses that infect bacterial cells and have been explored for their potential in treating bacterial infections. This review discusses the taxonomy of bacteriophages and the safety concerns in phage therapy. Although bacteriophages were initially considered safe for humans and animals, recent research indicates potential interactions with eukaryotic cells, raising questions about safety. Nevertheless, successful phage therapy cases have been reported, showing promising results in treating biofilm-based and multidrug-resistant infections. The use of bacteriophages has demonstrated minimal side effects and appears to be a viable alternative to traditional antibiotics. However, more research and controlled clinical trials are needed to fully understand the efficacy and safety of phage therapy in various clinical settings.